Identification of a Super-Spreading Chain of Transmission Associated with COVID-19 at the Early Stage of the Disease Outbreak in Wuhan - Hu, Ke; Zhao, Yang; Wang, Mengmei; Zeng, Qiqi; Wang, Xiaorui; Wang, Ming; Zheng, Zhishui; Li, Xiaochen; Zhang, Yunting; Wang, Tao; Zeng, Shaolin; Jiang, Yan; et al. (Archives of Clinical and Biomedical Research, 2021)
Background: The super-spreading events were associated with the outbreaks of SARS and MERS, but their association with the outbreak of COVID-19 was unknown before we first published a report in medRxiv preprint in March 2020. Here, we reported a super-spreading transmission chain of SARS-CoV-2 involving an index patient, seven cancer patients, 40 health care workers and four family members. Methods: We conducted a retrospective study to identify the index patient and the exposed individuals linked to a chain of transmission associated with COVID-19. We collected and analyzed the data on demographic features, exposure history, clinical presentation, laboratory investigation, radiological examination, and disease outcome of these patients. Results: We identified the index patient and another presumptive “super-spreader”, who initiated and amplified a super-spreading transmission chain associated with COVID-19, respectively. There were 31 female and 21 male patients in this cohort, and the median age was 37 years (range: 22-79 years). Each of them had an exposure history with the index patient or his close contacts. Approximately 87% (45/52) of the patients had fever or other symptoms, 96% (50/52) had abnormal chest CT-scan findings, 86% of the tested patients (39/45) were positive for SARS-CoV-2 in the nasopharyngeal or throat swab specimen, 85% of the tested patients (29/34) were positive for SARS-CoV-2-specific IgM and/or IgG, 15% of the RT-PCR positive patients were tested negative for the specific IgM and/or IgG at the convalescent phase, and 15% of the RT-PCR negative patients were tested positive for the specific IgM and/or IgG. The severe patients experienced a significant decrease in oximetry saturation, lymphocyte, and platelet counts, along with a significant increase in C-reactive protein, D-dimer, and lactate dehydrogenase. All six fatal cases h